Manajemen Sumber Daya Manusia Dalam Upaya Peningkatan Mutu Institusi Pendidikan - Fataruba, Sultia (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
Educational institutions are responsible for realizing the functions and objectives of national education. In this case, the principal has a very strategic role because one of the duties of the principal is to be a manager. The principal must be able to manage the whole school, including managing the existing human resources; especially the teachers and administrative staff who are the direct implementers of school activities who also play a major role in the success of the school in order to achieve the vision, mission and goals of the school. Resource management is carried out with several activities including preparation, organization, direction and supervision. In terms of human resource management, the principal has duties that are divided into three aspects, including: 1) equipping employees, 2) utilizing existing employees, and 3) building and developing. Supporting and inhibiting factors in human resource management must be managed properly so that good performance will be obtained, school goals can be achieved, and the quality of graduates will improve.